2008
DOI: 10.1016/j.socscimed.2007.11.023
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cumulative childhood adversity on young adult mental health: Measures, models, and interpretations

Abstract: Research studies investigating the impact of childhood cumulative adversity on adult mental health have proliferated in recent years. In general, little attention has been paid to the operationalization of cumulative adversity, with most studies operationalizing this as the simple sum of the number of occurrences of distinct events experienced. In addition, the possibility that the mathematical relationship of cumulative childhood adversity to some mental health dimensions may be more complex than a basic line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
216
2
4

Year Published

2010
2010
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(236 citation statements)
references
References 43 publications
14
216
2
4
Order By: Relevance
“…Socio-economic conditions during childhood affect health status during adulthood (Draper et al, 2008;Schilling et al, 2008). The greater the number of years spent living in poverty during childhood, the worse the adult health status becomes (Evans and Kim, 2007).…”
Section: Control Variablesmentioning
confidence: 99%
“…Socio-economic conditions during childhood affect health status during adulthood (Draper et al, 2008;Schilling et al, 2008). The greater the number of years spent living in poverty during childhood, the worse the adult health status becomes (Evans and Kim, 2007).…”
Section: Control Variablesmentioning
confidence: 99%
“…Recent advancements in neuroscience research have shed light on the importance of a child's earliest years for later adult health and well-being, as well as later economic activity (26,27) . Thus, a child's exposure to 'toxic stress' -the kind of emotional, psychological and physical stress associated with neglect, abuse and deprivation -has been shown to harm the child's current and future physical and mental health (27)(28)(29)(30) . In addition, recent research has identified how adversity that occurs in critical moments during childhood and adolescence has a decisive impact on behaviours, choices and social relationships that extend into adulthood (31) .…”
mentioning
confidence: 99%
“…The anticipated social consequences of low-paid or Finally, we also suggest that exposure to abusive or neglectful childhood conditions might have negative effects on either side of the proposed, problematic combination. In basic terms, severe exposure to stressors in early childhood resulting in long-term sensitisation may increase vulnerability to chronic stress under the kinds of social conditions indicated [18,49]. And deficits in early cognitive-behavioural development might contribute to a more limited set of strategies and skills to decisively resolve anticipated, aversive social events.…”
mentioning
confidence: 99%